Orientation changes near the interface of explosively bonded (carbon steel)/Zr700 sheets. Issue 1 (April 2015) - Paul, H; Baudin, T; Brisset, F; Prazmowski, M
Abstract: The microstructure and texture of explosively welded carbon steel (base) and Zr700 (flyer) plates were characterized by means of scanning electron microscopy equipped with a high resolution electron backscattered diffraction facility. The orientation maps demonstrate that the deformed zones near-the-interface are composed of several layers, the width of which depends on the applied bonding parameters. For both metals, the very thin layer of ultra-fine grains directly adheres to the interface. In the areas more distanced from the interface, the structure evolution depends on the plate material. In the case of a Zr 700 sheet the second layer is formed by highly dislocated (sub)grains, which progressively evolve, towards the structure composed of only lightly deformed grains. In the case of a carbon steel sheet, the second layer near the interface was composed of flattened grains.